Traffic offloading and its application in CRRM - Mohd Zaini, Khuzairi; Mohd Shariff, Azizul Rahman; Shi, Zheng (2014)
Common Radio Resource Management (CRRM) and traffic offloading are both promising approaches in the heterogeneous wireless networks (HWN) to increase overall resource efficiency and system performance. WLAN has been widely used as a complementary service for cellular network operator to offload their traffic. Based on traffic characteristics, user mobility and load balance we propose a new CRRM scheme that include traffic offloading functionality. When a user arrives in out of hot-spot area and no resource is available, the algorithm will identify some of the traffic to be offloaded in the overlap area from cellular network to WLAN and release the resource for the new user to use. The proposed approach also attempts to minimize unnecessary vertical handover (VHO) between cellular and WLAN. The effectiveness of the scheme is assessed analytically using the theory of 3D-Markov Chain. Numerical results demonstrate that the proposed CRRM scheme increase the overall system throughput, reduce the new call blocking probability and provide less service costs to the users.